ANALYSIS A POLICIES AND PRAXIS OF LAND ACQUISITION, USE, AND DEVELOPMENT IN NORTH SUMATERA - Ramayana Bachtiar (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
North Sumatera is one of the few Indonesia countries that have implemented a revolutionary land reform program that still retains the relics of the socialist ideology, specifically, the state ownership of land. Since 1975, the country has undergone a major transformation in implementing land reform policies and other major economic programs that have contributed to the development of an unsustainable land use structure that has become a burden on the national economy. The purpose of this research is to examine the current land use system in the context of the various policies and programs of the government. The analysis reveals that the land use system in North Sumatera is riddled with a host of problems including insecurity of tenure, fragmentation and diminution of farm sizes, corruption associated with land stocking by individuals and corporations with strong political ties, the dis-placement of farmers and poor urban residents, and the issue of expropriation and unfair compensation for land taken from land owners. The study recommends major reform programs related to right of ownership, land confiscation and compensation, institutional capacity building, protection of prime agricultural land and local environment, and addressing problems of landgrabbing and land banking.